2016
DOI: 10.15288/jsad.2016.77.77
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in Riding With an Alcohol/Drug-Impaired Driver From Adolescence to Emerging Adulthood in the United States

Abstract: ABSTRACT. Objective: The purpose of this study was to examine changes and predictors of changes in riding with an alcohol/drugimpaired driver (RWI) from 10th grade through the fi rst post-high school year. Method: Transition models were used to estimate the association of four waves (W1-W4) of RWI with W4 environmental-status variables and time-varying covariates in the NEXT Generation Health Study, a nationally representative cohort of U.S. 10th graders (N = 2,785). Results: Overall, 33% (weighted) of adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
(33 reference statements)
1
7
0
Order By: Relevance
“…In keeping with this pattern, more White non-Hispanic and Hispanic youth in our sample reported having substance-involved parents compared with other youth (17.3% vs. 9.4%, df = 1, p < .01, unpublished data). Interestingly, residence urbanicity did not affect RWDD-AH risk in this study, similar to other studies (Leadbeater et al, 2008;Vaca et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In keeping with this pattern, more White non-Hispanic and Hispanic youth in our sample reported having substance-involved parents compared with other youth (17.3% vs. 9.4%, df = 1, p < .01, unpublished data). Interestingly, residence urbanicity did not affect RWDD-AH risk in this study, similar to other studies (Leadbeater et al, 2008;Vaca et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Although several prior studies examined adolescents' RWDD (Kann et al, 2014;Li et al, 2014;Poulin et al, 2007;Vaca et al, 2016), we found only one other study that specified riding with an adult drinking driver. In 2006, an anonymous survey of 2,594 Canadian 10th-12th graders found a lifetime prevalence of more than 50% reporting ever riding in a car with a drinking driver who was older than age 25 (Leadbeater et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys can provide a wealth of information on potential contributing factors and are a rare source of information about driver attitudes and other dispositions. In ongoing research, my team annually examines in a national cohort of adolescents and young adults self‐reported risky driving behavior, including unsafe driving practices, potentially distracting secondary task engagement, and impaired driving …”
Section: Transportation Research Methodsmentioning
confidence: 99%
“…In ongoing research, my team annually examines in a national cohort of adolescents and young adults self-reported risky driving behavior, including unsafe driving practices, potentially distracting secondary task engagement, and impaired driving. 21,22…”
Section: Survey Researchmentioning
confidence: 99%